Research on the Measured Ventilation Effect of the Chemical Lab Building. (2017) - Han, Rubing; xu, Zhimao; Wang, Liang; Qing, Yutao
Abstract: Chemical lab building ventilation has immediate impact on teachers' and students' physical health. This paper studies the ventilation system of a university's chemical lab building in Mianyang. The ventilation system of chemical lab building combines mechanical exhaust ventilation with natural supply wind through windows. The research group select two typical ventilation systems under stable condition to test the wind speed of natural ventilation through windows, fume hood exhaust inlets and the general exhaust ventilation vents. Meanwhile, it also tests roof exhaust air speed of the vertical ducts. It evaluates the ventilation difference between the actual working condition and the design condition; it also evaluates the actual effect of ventilation system, through comparing actual and design conditions. At the same time, suggestions are put forward for the lab ventilation system design.